#TITLE_ALTERNATIVE# - (NIM 30503001), NOERATI
Cellulose material is the most widely used fiber for textile materials, although nowadays there are a number of synthetic fibers production such as polyester and polyamide. Cellulose fibers is generally used as clothing, sports textile, and household textile such as bed cover, blanket, and even medical textile such as surgical mask, bandages, and surgical gowns cloth. The superior characteristic of cellulose fibers lies in its worn comfort because it has high moisture regain. However, cellulose fibers have disadvantage properties such as low crease resistant and good media for bacterial regeneration. Anti bacterial characteristic is not only important feature for medical textile but also for clothing and household textile. To enhance anti crease properties of cotton, a methylol derivative compound is usually added into cellulose fibers so that can crosslinks occur between each cellulose chain. This compound has also anti septic properties. The disadvantage of this compound is that it can release free formaldehyde during the process or storage which can reduce anti-septic properties and can danger human health. Copper or zinc metal salts are commonly used as anti bacterial agents of textile materials. In line with the increased awareness of the environmental issue, those hazarding compounds are prohibited to be used in textile processing. The goals of this research are to synthesize chitosan esters which have anti bacterial and anticrease properties. In this work, chitosan succinate, glutarate and citrate have been successfully synthesized to fulfill those two functions. The advantage of carboxylic chitosan derivatives are can carry covalent bond with cellulose so that the result is permanent antibacterial properties and simultaneously it can enhance crease recovery of cellulose fabric. The role of chitosan sucinate, chitosan glutarate and chitosan citrate as an anti crease and anti bacterial agent for cotton is a new finding of this research. The first stage of this research included the selection of dicarboxylic derivatives used as anti crease compounds. The objective of this stage is to obtain several carboxylic acids that can be used as anti crease compounds. To optimize the ester bond formation the concentration of carboxylic acid and catalyst were varied. The characterizations of the products comprised of identification of ester group with FTIR (Fourir Transformn Infra Red), crease resintance, and tensile strength of fabric. It was found that among six dicarbocylic derivative compounds (oxalic acid, malonic acid, maleic acid, succinic acid, glutaric acid, and citric acid) four compounds could be used as crease resistant compound i.e. maleic acid, succinic acid, glutaric acid, and citric acid. Larger carboxylic derivatives resulted in higher crease resistant. The optimum condition of the first stage was obtained in using 6 of % carboxylic derivative concentration and sodium dihydrogen phosphate as catalyst. The second stage was the synthesis of carboxylic-chitosan through esterification reaction between chitosan and dicarboxylic derivatives. The esterification experiments were carried out through varied reaction times and mol ratio between chitosan and dicarboxylic derivatives. The resulted chitosan derivatives were characterized with FTIR and 1H-NMR (Nuclear Magnetic Resonance) for molecular structure elucidation, XRD (X-Ray Diffraction) to determine crystallinity, TGA/DTA (Thermogravimetry Analysis/Deferential Thermal Analysis) to show thermal properties, and solubility in water. The FTIR spectrum proved that carboxylic group was substitued into chitosan, because a new absorption peak appeared at around 1719 cm-1 attributed to carbonyl absorption of the carboxylic group Characteristic peak around 1631 cm-1 indicated amide I band. These facts were also supported by 1H NMR spectrum which shows carboxylic substitution at 2.2 to 2.6 ppm attributed of methylene proton of the carboxylic derivatives compound. While the degree of crystallinity in the XRD difractogram is decreased, it shows that carboxylic derivatives in chitosan chain were substituted. Thermogram analysis shows that there is higher dehydration occurred in the chitosan derivatives because polar carboxylic groups in chitosan has been substituted and resulted an increase in moisture regain of chitosan derivatives. The solubility properties of chitosan derivatives in water showed substituted carboxylic groups, which had maximum solubility of 50 g/L. It was found that the optimum condition of esterification process of chitosan was 20 hours of reaction time and ratio of 1 : 6 between mol of chitosan and mol of dicarboxylic derivative. The third stage of this work was the esterification process of cotton fabric as cellulose materials which have been carried out with varied concentration of water soluble chitosan. The esterified cotton was characterized for its properties as follows: antibacterial, crease resistant, mechanical properties and thermal properties. The results showed that the crease resistant and antibacterial properties of the esterfied cotton fabrics were improve and durable in ten cycle washing times in Laundre ÃƒÂƒÃ‚ÂƒÃƒÂ‚Ã‚Â‚ÃƒÂƒÃ‚Â‚ÃƒÂ‚Ã‚Â‘O meter machine which is similar to 50 cycle domestic washing. Cross linking each cellulosic chains by chitosan derivatives was proven by fiber swelling test which showed that the degree of swelling of esterified cotton was smaller than that of standard cotton. The elasticity modulus of esterified cotton fabric and standard cotton showed that esterified cotton is stiffer than unesterified cotton. These resulted showed that the optimum condition of chitosan derivatives for cotton esterification was 0.8% in which the three types of esterified cotton fabrics were able to decrease bacteria population up to 84%, and have anti crease properties according to SNI standard. It can be concluded that the dicarbocylic derivatives of chitosan showed a potency to replace the metylol derivaties as well as the salts of cupro and zinc.